2011
DOI: 10.1590/s1807-59322011000400023
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of basolateral amygdaloid neuronal dendritic arborization following Bacopa monniera extract treatment in adult rats

Abstract: OBJECTIVE:In the ancient Indian system of medicine, Ayurveda, Bacopa monniera is classified as Medhya rasayana, which includes medicinal plants that rejuvenate intellect and memory. Here, we investigated the effect of a standardized extract of Bacopa monniera on the dendritic morphology of neurons in the basolateral amygdala, a region that is concerned with learning and memory.METHODS:The present study was conducted on 2½-month-old Wistar rats. The rats were divided into 2-, 4- and 6-week treatment groups. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…This study has demonstrated that treatment with Bacopa monnieri significantly suppressed the evoked nociceptive responses when orally administered daily in doses of 40 and 80 mg/kg, which were tolerable and benign based on the toxicity profile [31, 80]. Similar doses of Bacopa monnieri have been shown to possess significant neuroprotective effects including its ability to protect the cerebral cortex [81], enhance dendritic length and arborization of amygdala [71] and hippocampal CA 3 neurons [72]. Moreover, these doses also have significant anti-stress and anti-depressant activities [38, 82] and neuropathic pain is often associated with comorbidities such as anxiety and depression, resulting in a low health-related quality of life [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has demonstrated that treatment with Bacopa monnieri significantly suppressed the evoked nociceptive responses when orally administered daily in doses of 40 and 80 mg/kg, which were tolerable and benign based on the toxicity profile [31, 80]. Similar doses of Bacopa monnieri have been shown to possess significant neuroprotective effects including its ability to protect the cerebral cortex [81], enhance dendritic length and arborization of amygdala [71] and hippocampal CA 3 neurons [72]. Moreover, these doses also have significant anti-stress and anti-depressant activities [38, 82] and neuropathic pain is often associated with comorbidities such as anxiety and depression, resulting in a low health-related quality of life [83].…”
Section: Discussionmentioning
confidence: 99%
“…Bacopa monnieri extract was orally administered daily in doses of 40 and 80 mg/kg [71, 72]. Gabapentin, used as a positive control, was intraperitoneally administered once daily at a dose of 75 mg/kg [73].…”
Section: Methodsmentioning
confidence: 99%
“…These traditional claims have recently been supported by several animal and clinical studies. Animals treated chronically with Bacopa showed better acquisition and improved retention in learning tasks [ 3 11 ]. Similarly, clinical studies and a meta-analysis of randomized control trials also demonstrated that chronic oral administration of Bacopa (over a period of more than 12 weeks) to healthy subjects resulted in improvements in the subjects’ information processing speed, free recall, verbal memory and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Vollala et al 126 studied the effect of BM on the dendritic morphology of neurons in the basolateral amygdala, a region implicated in learning and memory. Twenty-four rats were divided into 2-, 4-, and 6-week treatment groups, and then further divided into 20, 40, and 80 mg/kg per os (p.o.)…”
mentioning
confidence: 99%
“…Camera lucida tracings of basolateral amygdaloid neurons from control rats (A) and rats treated with Bacopa monniera for 6 weeks at doses of 20 mg/kg (B), 40 mg/kg (C), and 80 mg/kg (D). (Reprinted, with permission, from Vollala et al126 …”
mentioning
confidence: 99%